Acanthosis nigricans and "tripe palm" as paraneoplastic manifestations of metastatic tumor Acantose nigricante e "palma em tripa" como manifestações paraneoplásicas de tumor metastático - Mariana Carvalho Costa; Nayibe Solano Martinez; Maluf Gabbay Belicha; Fabiano Leal (Anais Brasileiros de Dermatologia, 2012)
Acanthosis nigricans is a common dermatosis and is most often associated with benign conditions, such as insulin resistance. It is rare as a paraneoplastic marker. As such, it is characterized by sudden onset and rapid dissemination of velvety and hyperchromic skin lesions. The term "tripe palm" refers to exaggeration of the palmar ridge pattern, which resembles the internal surface of the bovine intestinal tract. This is a paraneoplastic marker of high specificity, with 90% of the cases being associated with malignancy. We report the case of a patient with stage IV ovarian adenocarcinoma presenting acanthosis nigricans and tripe palm. Both findings are closely correlated to the neoplasm course. A acantose nigricante é uma dermatose comum, mais frequentemente associada a condições benignas, como resistência periférica à insulina. É rara como marcador paraneoplásico. Como tal, é caracterizada pelo aparecimento repentino e disseminação rápida de lesões cutânas aveludadas e hipercrômicas. O termo "palma em tripa" se refere ao aumento da demarcação do sulcos cutâneos, que se assemelha à face interna do trato intestinal bovino. É um marcador paraneoplásico de alta especificidade, com 90% dos casos associados à malignidade. Relatamos uma paciente com adenocarcinoma de ovário, estágio IV, apresentando acantose nigricante e "palma em tripa"; ambos achados estão estreitamente relacionados ao curso da neoplasia.